LEGAL AND NORMATIVE INSTRUMENTS IN CIVIL CONSTRUCTION WASTE MANAGEMENT IN BRAZIL - Lockstein, Scheila; Chaves Nogueira, Maria Rita; Soares, Petrick Anderson (Anais eletrônicos do International Symposium on Science and Biotechnology, 2017)
Civil construction waste (CCW) cause to financial and logistical problems and is environmentally degrading. This work describes the legal basis and guidelines governing the management of CCW in Brazil. The Brazilian legal framework in the area began around 1981, with the National Environmental Politics. However, only in 2010 was promulgated the National Politics on Solid Waste (PNRS). In an innovative way, the PNRS establishes an order of priority for waste management, from non-generation to treatment and waste disposal. The National Environmental Council (CONAMA) through resolution 307/02 establishes guidelines, criteria and procedures for the management of CCW. Later, some items and articles of this resolution were changed by the Resolutions 348/04, 431/11, 448/12 and 469/15. On the other hand, the Brazilian Association of Technical Standards through the (NBR) 10004 defines waste and classifies them according to the physical nature, chemical composition and potential risk to the environment. In 2004, it published a set of norms referring to the solid waste of the civil construction stands out NBR 15114, 15115 and 15116. Finally, there is a legal and technical structure that guides and norms the management of CCW in the country, with emphasis on PNRS and CONAMA Resolution 307/02.